Continuity and change in American urban freeway networks. (January 2017) - Weber, Joe
Abstract: The American Interstate Highway System was created in 1944, though construction did not commence until 1956. During the planning process for this network the blueprint for American urban freeway systems was set in 1955 by a federal document called the Yellow Book. This provided about 100 maps of cities with planned urban freeway locations for the Interstate Highway System. A set of three basic network patterns were applied to these cities based on their size and location. In the half century since 1955 urban freeways in the Interstate System have expanded from a planned 2000 miles to over 16, 600 miles, along with another 11, 500 miles of non-Interstate freeways. The number of large metropolitan areas has increased tremendously while the monocentric commuting patterns of have been transformed. This paper explores how these urban freeway systems were applied to the country's urban geography of the 1950s and how they have adapted to changing populations and other transformations in American metropolitan areas in the last half century. Highlights: 1955 Yellow Book provided basis for urban freeway systems. Yellow Book maps do not fit population patterns. Compare 1955 and 2010 pattern Freeway network categories of little use in describing cities